Is the United States CPI Biased Across Income and Age Groups? - Erbas, S.; Sayers, Chera (Washington, D.C. : International Monetary Fund, 1998)
The recent Boskin Commission Report (1996) underscores a significant upward bias in CPI measurement in the United States. This may result in excessive cost-of-living adjustment (COLA) of some entitlements in the federal budget because COLA is indexed to CPI. This paper presents some evidence that overall CPI may be biased against lower income elderly households, the primary beneficiaries of COLA. Although a downward adjustment in CPI resulting in an across-the-board cut in COLA of entitlements may yield significant budgetary savings, it may result in a deterioration in income distribution against lower income elderly households.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet